Feasibility study of the binary geopolymer as the dredged silt stabilizer. Issue 1 (February 2021) - Shi, Yupeng; Zhang, Mo; Pan, Zhu; Sanjayan, Jay
Abstract: With the increasing dredging activities, a large quantity of silt is removed from the bottom of waterbody and dumped on the landfill site, having the potential to cause a number of environmental issues. Given that dredged silt is the soft and weak soil, it is usually stabilized with ordinary Portland cement (OPC) and/or lime for application in construction. However, the production processes of traditional stabilizers are energy intensive and high CO2 emission. In this study, attempts are being made to find an alternative environmentally friendly stabilizer with a low carbon footprint using industrial by-products. Six mixtures were prepared and these mixes can be grouped into two series. Series I includes untreated soil (S), cement stabilized soil (CS), the binary geopolymer (alkali-activated slag-fly ash) stabilized soil (SFS) and the alkali-activated soil (AS). In series II, 18% sand (by the weight of total soil) was added to SFS and AS. The properties of stabilized soils were evaluated via unconfined compressive strength (UCS) test, scanning electron microscopy (SEM) imaging and X-ray diffractometer (XRD) test. The results showed the formation of geopolymer gel for both AS and SFS. The formation of sodium alumino silicate hydrate was also detected, which may result in higher strength of SFS, as compared to AS. The strength of SFS is similar to that of CS while the emission CO2-e values of SFS are 76% lower than that of CS, indicates the effectiveness of the binary geopolymer as an effective and green soil stabilizer alternative to OPC.